Analisa Diplomasi Budaya Indonesia Melalui Tari Saman Gayo Dalam Mengukuhkan Identitas Nasional Bangsa - SD, Hardi Alunaza (Universitas Muhammadiyah Yogyakarta, 2015)
Diversity of Indonesian culture must be maintained by preserving and protecting from the claim of another country. This paper is aim to explain how the existence of traditional culture is very important. In fact, it has big role in shaping the national identity. The writer using national identity concept to analyze this phenomena. Indonesia is doing diplomacy by proposing Saman Gayo Dance as intangible cultural heritage original from Indonesia to UNESCO. This is done in order to preserve Saman dance from extinction and functioned as affirmation of the national identity of Indonesia.